Cyclic softening behaviors of ultra-fine grained Cu-Zn alloys. (December 2016) - Zhang, Z.J.; Zhang, P.; Zhang, Z.F.
Abstract: Low-cycle fatigue tests were carried out on ultra-fine grained (UFG) Cu and Cu-Zn alloys to reveal the mechanisms of cyclic softening and the effects of dislocation slip mode. Based on careful examinations of the grain coarsening (GC), shear band (SB) evolutions and surface hardness change during cyclic deformation, the microscopic mechanisms of the cyclic softening process and the correlations between GC and SBs were deeply revealed. Besides, a general and coincident relationship was found between the softening velocities and the fatigue lives for UFG Cu and Cu alloys. Finally, it is approved that through alloying to increase the slip planarity, the cyclic softening caused by GC and SBs can be largely restrained such that the fatigue life may be improved effectively. Graphical abstract: Formation mechanism of shear bands in UFG metals during low-cycle fatigue.